2004
DOI: 10.1177/031289620402900204
|View full text |Cite
|
Sign up to set email alerts
|

Australian Evidence Concerning the Information Content of Economic Value-Added

Abstract: Pooled time-series, cross-sectional data on 110 Australian companies over the period 1992-1998 is employed to examine whether the trademarked variant of residual income known as economic value-added (EVA ®) is more highly associated with stock returns than other commonly-used accounting-based measures. These other measures of internal and external performance include earnings, net cash flow and residual income. Three alternative formulations for pooling data are also employed in the analysis, namely, the commo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
58
2
7

Year Published

2010
2010
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(77 citation statements)
references
References 20 publications
10
58
2
7
Order By: Relevance
“…For example, Worthington and West (2004) investigated the accounting measures (earnings before extraordinary items (ERN) and net cash flows from operations (NCF)) and economic measures (residual income (RI) and EVA) to find out which variable has the largest relative information content. Their research was on 110 Australian firms over the period 1992-1998 and they showed that EVA has the largest relative information content among others.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, Worthington and West (2004) investigated the accounting measures (earnings before extraordinary items (ERN) and net cash flows from operations (NCF)) and economic measures (residual income (RI) and EVA) to find out which variable has the largest relative information content. Their research was on 110 Australian firms over the period 1992-1998 and they showed that EVA has the largest relative information content among others.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Cross sectional analysis of the sample firms has been done using the tool of Regression Analysis. Another study for (Worthington and West, 2004), Pooled time-series, cross-sectional data on 110 Australian companies over the period 1992-1998 was employed to examine whether the trademarked variant of residual income known as economic value-added (EVA) was more highly associated with stock returns than other commonly-used accounting-based measures. These other measures of internal and external performance include earnings, net cash flow and residual income.…”
Section: Previous Studiesmentioning
confidence: 99%
“…However, having identified that many scholars confirmed the findings of EVA promoters (for example; O'Byrne, 1996;Uyemura, Kantor and Petit, 1996;Milunovich and Tsuei,1996;Lehn and Makhija,1997;Herzberg,1998;and Forker and Powell, 2004;Worthington and West , 2004;Haddad, 2012) there are sufficient number of researchers (Peterson and, Peterson, 1996;Appleby, 1997;Turvey et al ,2000;Garvey and Milbourn, 2000;Keefand Rush, 2003;Sparling and Turvay, 2003;Paulo, 2003;Threemanna and Gunaratne, 2015)who have concluded in contrary to EVA proponents argument on the value relevance of EVA.…”
Section: Introductionmentioning
confidence: 99%